PERMAINAN EDUKATIF MEDIA PUZZLE WARNA-WARNI UNTUK MELATIH MOTORIK HALUS PADA ANAK TK IT FATHIYYAH KOTA PALEMBANG - Mardiana Mardiana; Mutia Mawardah (LPPM Universitas Bina Bangsa, 2023)
Basically, the implementation of education in kindergarten must be able to create a safe and comfortable playing environment as a vehicle for children's growth and development. Specifically, the purpose of this research is to find out about the application of colorful puzzle media educational games to train fine motor skills in TK IT Fathiyyah in Palembang City. The methods used, namely: observation, interviews, preparation, implementation, evaluation. The results of this educational activity the author discusses a problem and provides a solution, namely training students' fine motor skills with educational game tools. Educational Game Tool (APE) is one of the learning media that is very suitable for early childhood